EMPOWERMENT OF FARMER GROUPS BY THE AGRICULTURAL EXTENSION CENTER IN KALAPASAWIT VILLAGE LAKBOK DISTRICT CIAMIS REGENCY : Array - Widyawati; Lina Marliani; Ahmad Juliarso (JGSRD: Journal of Government Science and Rural Development, 2022)
Research conducted concerning the implementation of Empowerment of Farmer Groups by the Agricultural Extension Center (BPP) in kalapasawit village, Lakbok subdistrict, Ciamis regency started from a problem, lack of communication in providing direction for the improvement of farmer groups in empowerment activities, lack of agricultural extension in providing awareness of the importance of agriculture to farmer groups by giving appropriate recommendations in utilizing yard land to improve farming, and agricultural extensionists are less able to strengthen community participation for the development of farming that has not been optimal because of limited capital from the community. In this study the authors used qualitative research methods. The data collection techniques used by the authors in this study are observation techniques and interview techniques. As for the informant in this study as many as 7 (seven) people. Based on the results of the study can be known that empowerment by the Agricultural Extension Agency (BPP) in kalapsawit village Lakbok District Ciamis district as a whole has been running but still not optimal, seen there are still indicators that are not appropriate in its implementation such as lack of cooperation, lack of meetings to glue friendship, still lack of extension workers that cause a lack of focus in providing guidance and training, still a lack of awareness in terms of keeping farmer groups from falling into increasingly weak positions, lack of communication, lack of community participation in addressing the problems faced and lack of public awareness in utilizing the yard. The efforts in overcoming these obstacles are by improving human resources optimally, as well as developing information media and socialization or trainings provided directly by agricultural extensionists.